Changes in the Cropping Pattern, Crop Concentration, Agricultural Efficiency in Papanasam Taluk, Thanjavur District, Tamil Nadu, India - R. Baskaran, J. Punithavathi* (Recent Research in Science and Technology, 2010)
Cropping pattern simply means the proportion of area under different crops at a point of time, where us change in cropping pattern refers to the change in proportion of area under different crops at two different points of time. The cropping pattern of any area is generally controlled by physical, socio economic and technological factors. There are more than 20 crops with varying hectares are grown in this taluk. Of these 20 crops only 5 crops based on the properties of land to the total area under cultivation alone has been considered for analysis. Simple percentage obtained by dividing total area under crops, in to area of different crops. Paddy is the dominant crop in this taluk. During the year 1995-1996 to 2008-2009 the following are the major 5 major crops are taken in to cultivate in the study area. Such as Paddy 82.2%, Sugarcane 6.5%, Oilseeds 4.5%, Pulses 4.1% and Cotton 1.9% to the total cropped area in the taluk.